PERBEDAAN PENGARUH LATIHAN SKIPPING DAN SQUAT JUMP TERHADAP POWER OTOT TUNGKAI SISWA EKSTRAKURIKULER BOLA VOLI SMK MUHAMMADIYAH 1 JATINOM KLATEN - Fajar Setyawan; Slamet Santoso; Satrio Sakti Rumpoko, (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2023)
This study aimed (1) to determine the effect of skipping exercises on leg muscle power of volleyball extracurricular students at SMK Muhammadiyah 1 Jatinom Klaten, (2) to determine the effect of squat jump exercises on the leg muscle power of volleyball extracurricular students at SMK Muhammadiyah 1 Jatinom Klaten, (3) to find out the differences in the effect of skipping and squat jump exercises on the leg muscle power of volleyball extracurricular students at SMK Muhammadiyah 1 Jatinom Klaten. This study is experimental method with the design "Two Groups Pretest Posttest Design" The population in this study were volleyball extracurricular students at SMK Muhammadiyah 1 Jatinom Klaten, totaling 46 students. The sample taken from the results of purposive sampling, with the criteria of being male. Based on these criteria, there were 40 students who fulfilled it. The instrument used to test leg muscle power is a vertical jump. Data analysis using the t test. From the result of analysis: (1) there is an effect of skipping exercises on leg muscle power of volleyball extracurricular students at SMK Muhammadiyah 1 Jatinom Klaten, with t count 15.70 > t table 2.093, and a significance value of 0.000 <0.05, the percentage increase is 8%, (2) there is an effect of squat jump exercise on leg muscle power of volleyball extracurricular students at SMK Muhammadiyah 1 Jatinom Klaten, with t count  15.20 > t table 2.093, and a significance value of 0.000 <0.05, a percentage increase of 6%, (3) skipping exercise is better than squat jump exercise to increase leg muscle power in volleyball extracurricular students at SMK Muhammadiyah 1 Jatinom Klaten, the percentage increase is 8%.